Agent-based conference management: a case study in SODA. (3rd December 2009) - Molesini, Ambra; Denti, Enrico; Omicini, Andrea
Conference management is concerned with managing the dependencies of activities required to produce the proceedings of a scientific conference. This case study, very frequently used in the literature, presents interesting software engineering issues because it involves a number of articulated coordination activities and stresses interaction between peers. This paper presents an agent-based solution to the conference management problem using the Societies in Open and Distributed Agent spaces (SODA) agent-oriented methodology. On the one hand, this demonstrates the general benefits of Agent-Oriented Software Engineering (AOSE); on the other hand, it emphasises the peculiarities of SODA: in particular, its focus on inter-agent, social aspects and its layering mechanisms for handling the engineering of complex computation systems. We first discuss why conference management is interesting from the AOSE viewpoint, then we show how to face the many issues in the design of its software architecture by means of SODA.